Generic icons – yes or no? - Bedi, Krunoslav; Žajdela Hrustek, Nikolina (Journal of Information and Organizational Sciences, 2010)
The information society has become increasingly dependant on programs that are subjected to frequent evolutive, basic and logical changes for a variety of reasons whereas the visual design of the program/program interface mostly remains the same or gets slightly modified. The development of technology has become to such an extent a commonplace that the use of redesigned programs implies icons that are visually acceptable although representing obsolete technologies and that are eventually hard to change due to the habits developed by the program users. The research presents a study into the personal preference as to a particular icon, “Save” for example, and into the perception of the visual identities of today’s programs under the circumstance of program icons being not compliant with the technological state-of-the-art. Based on the obtained results, the survey that included students attending web design and media technician courses and ECDL course participants who come in contact with computers and programming tools for the first time should enlighten both teachers and designers of programming interfaces about the way of linking the formal knowledge with a constructivist approach to designing and redesigning programs.